Evolution and simplified terminology of natural orifice transluminal endoscopic surgery (NOTES), laparoendoscopic single-site surgery (LESS), and mini-laparoscopy (ML) - Georgiou, Alexandros N.; Rassweiler, Jens (World journal of urology, 2012)
IntroductionNatural orifice transluminal endoscopic surgery (NOTES) and laparoendoscopic single-site surgery (LESS) are the next steps in the evolution of laparoscopic surgery, promising reduced morbidity and improved cosmetic result. The inconsistent terminology initially used led to confusion. Understanding the technical evolution, the current status and a unified and simplified terminology are key issues for further acceptance of both approaches.ObjectiveTo present LESS and NOTES in its historical context and to clarify the associated terminology.MethodExtensive literature search took place using the PubMed. Several hundred publications in general surgery and urology regarding LESS are present including the expert opinion of members the European Society of Uro-technology (ESUT).ResultsThe increasing interest on NOTES and LESS is reflected by a raising number of publications during the last 4 years. The initial confusion with the terminology of single-incision surgery represented a significant issue for further evolution of the technique. Thus, consortiums of experts searched a universally acceptable name for single-incision surgery. They determined that ‘laparoendoscopic single-site surgery’ (LESS) was both scientifically accurate and colloquially appropriate, the term being also ratified by the NOTES working group (Endourological Society) and the ESUT. For additional use of instruments, the terms hybrid NOTES and hybrid LESS should be used. Any single use of miniaturized instruments for laparoscopy should be called mini-laparoscopy.DiscussionThe evolution of LESS and most likely NOTES to a new standard of minimally invasive surgery could represent an evolutionary step even greater than the one performed by the establishment of laparoscopy over open surgery.
Gesehen am 04.05.2018